Tapered channel for six-dimensional muon cooling towards micron-scale emittances - Diktys Stratakis; Richard C. Fernow; J. Scott Berg; Robert B. Palmer (Physical Review Special Topics. Accelerators and Beams, 2013)
A high-luminosity muon collider requires a significant reduction of the six-dimensional emittance prior to acceleration. Obtaining the desired final emittances requires transporting the muon beam through long sections of a beam channel containing rf cavities, absorbers, and focusing solenoids. Here we propose a new scheme to improve the performance of the channel, consequently increasing the number of transmitted muons and the lattice cooling efficiency. The key idea of our scheme is to tune progressively the main lattice parameters, such as the cell dimensions, rf frequency, and coil strengths, while always keeping the beam emittance significantly above the equilibrium value. We adopt this approach for a new cooling lattice design for a muon collider, and examine its performance numerically. We show that with tapering the cooling rate is not only higher than conventional designs, but also maintains its performance through the channel, resulting in a notable 6D emittance decrease by 3 orders of magnitude. We also review important lattice parameters, such as the required focusing fields, absorber length, cavity frequency, and voltage.